Cadexomer iodine provides superior efficacy against bacterial wound biofilms in vitro and in vivo. Issue 1 (5th December 2016) - Fitzgerald, Daniel J.; Renick, Paul J.; Forrest, Emma C.; Tetens, Shannon P.; Earnest, David N.; McMillan, Jillian; Kiedaisch, Brett M.; Shi, Lei; Roche, Eric D.
Abstract: Examination of clinical samples indicates bacterial biofilms are present in the majority of chronic wounds, and substantial evidence suggests biofilms contribute significantly to delayed healing. Bacteria in biofilms are highly tolerant of antimicrobials, and little data exist to guide the choice of anti‐biofilm wound therapy. Cadexomer iodine (CI) was recently reported to have superior efficacy compared to diverse wound dressings against Pseudomonas aeruginosa biofilms in an ex vivo model. In the current study, the strong performance of CI vs. P. aeruginosa biofilm was confirmed using colony and colony drip‐flow in vitro wound biofilm models. Similar in vitro efficacy of CI was also demonstrated against mature Staphylococcus aureus biofilms using the same models. Additionally, the rapid kill of mature S. aureus and P. aeruginosa colony biofilms was visualized by confocal microscopy using Live/Dead fluorescent stains. Superior in vitro efficacy of CI vs. staphylococcal biofilms was further demonstrated against methicillin‐resistant S. aureus (MRSA) using multiple biofilm models with log reduction, Live/Dead, and metabolic endpoints. Comparator antimicrobial dressings, including silver‐based dressings used throughout and other active agents used in individual models, elucidated only limited effects against the mature biofilms. Given the promising in vitro activity, CI was tested in an established mouse model of MRSA wound biofilm. CI had significantly greater impact on MRSA biofilm in mouse wounds than silver dressings or mupirocin based on Gram‐stained histology sections and quantitative microbiology from biopsy samples (>4 log reduction in CFU/g vs. 0.7–1.6, p  < 0.0001). The superior efficacy for CI in these in vitro and in vivo models suggests CI topical products may represent a better choice to address established bacterial biofilm in chronic wounds.